BRIDGING CULTURE AND TECHNOLOGY: A PROJECT-BASED LEARNING BASED 3D ANIMATION FILM FOR MOTIVATING STUDENTS IN MATHEMATICS - Sabil, Husni; Novferma, Novferma; Huda, Nizlel; Romundza, Febbry (LPPM Universitas Jambi, 2025)
Low motivation among students in learning mathematics, which is often viewed as abstract and disconnected from everyday life, remains a persistent challenge in Indonesian education. This study aims to develop and test the effectiveness of a 3D animated film based on ethnomathematics integrated with the Project-Based Learning (PjBL) model to enhance students’ learning motivation and cultural appreciation. The research employed a Research and Development (R&D) approach following Borg and Gall’s model through several stages: product design, expert validation, preliminary trials, field implementation, and operational evaluation. The participants consisted of junior high school students divided into control and experimental groups. Data were collected through expert validation sheets, student response questionnaires, and learning motivation scales. The validation results indicated that the 3D animated film achieved a score of 82%, categorized as “good” and suitable for classroom implementation. Statistical analysis revealed a significant increase in learning motivation in the experimental group compared to the control group, as evidenced by higher pretest–posttest gain scores. The novelty of this study lies in the integration of 3D animation and ethnomathematics within the PjBL framework an innovative combination that contextualizes mathematical concepts through local cultural wisdom while promoting active, project-based engagement. This research contributes to the growing field of culturally responsive digital learning media by demonstrating that ethnomathematics-based animation not only enhances motivation but also bridges traditional cultural values with modern technological learning approaches, offering a scalable model for 21st-century mathematics education.